Precision Genome Editing Techniques in Gene Therapy: Current State and Future Prospects - Singh, Kuldeep; Bhushan, Bharat; Kumar, Sunil; Singh, Supriya; Macadangdang, Romulo R.; Pandey, Ekta; Varma, Ajit K.; Kumar, Shivendra (Current Gene Therapy, 2024)
Precision genome editing is a rapidly evolving field in gene therapy, allowing for the precise modification of genetic material. The CRISPR and Cas systems, particularly the CRISPRCas9 system, have revolutionized genetic research and therapeutic development by enabling precise changes like single-nucleotide substitutions, insertions, and deletions. This technology has the potential to correct disease-causing mutations at their source, allowing for the treatment of various genetic diseases. Programmable nucleases like CRISPR-Cas9, transcription activator-like effector nucleases (TALENs), and zinc finger nucleases (ZFNs) can be used to restore normal gene function, paving the way for novel therapeutic interventions. However, challenges, such as off-target effects, unintended modifications, and ethical concerns surrounding germline editing, require careful consideration and mitigation strategies. Researchers are exploring innovative solutions, such as enhanced nucleases, refined delivery methods, and improved bioinformatics tools for predicting and minimizing off-target effects. The prospects of precision genome editing in gene therapy are promising, with continued research and innovation expected to refine existing techniques and uncover new therapeutic applications.
Keywords: genetic disorders